Current and investigational drugs in early clinical development for portal hypertension - Sakiani, Sasan; Heller, Theo; Koh, Christopher (Frontiers in Medicine, 2022)
Introduction: The development of portal hypertension leads to the majority of complications associated with chronic liver disease. Therefore, adequate treatment of portal hypertension is crucial in the management of such patients. Current treatment options are limited, and consist mainly of medications that decrease the hyperdynamic circulation, such as non-selective beta blockers, and treatment of hypervolemia with diuretics. Despite these options, mortality rates have not improved over the last two decades. Newer, more effective treatment options are necessary to help improve survival and quality of life in these patients. Areas Covered: Multiple preclinical models and clinical studies have demonstrated potential efficacy of a variety of new treatment modalities. We introduce treatment options including the use of vasodilation promotors, vasocontriction inhibitors, anticoagulants, antiangiogenics, and anti-inflammatories. We examine the most recent studies for treatment options within these drug classes and offer insights as to which show the most promise in this field. Methodology: Published literature searches were performed using Pubmed (https://pubmed.ncbi.nlm.nih.gov/) that identified novel medical treatment options of portal hypertension. Clinical trials listed with Clinicaltrials.gov were also searched with focus on more recent and ongoing studies, including those with completed recruitment. Search terms included “portal hypertension” as well as individually searching specific treatment medications that were listed in other publications. Finally, current societial guidelines and recent review articles relevant to the management of portal hypertension were evaluated and listed references of interest were included. Conclusion: Many ongoing early phase studies demonstrate promising results and may shape the field of portal hypertension management in the future. As concrete results become available, larger RCTs will be required before making definitive conclusions regarding safety and efficacy and whether or not they can be incorporated into routine clinical practice. Statins, anti-coagulants, and PDE inhibitors have been amongst the most studied and appear to have the most promise.